Evidence on the pathogenic role of auto-antibodies in acute cardiovascular diseases - Carbone, Federico; Nencioni, Alessio; Mach, François; Vuilleumier, Nicolas; Montecucco, Fabrizio (Thrombosis and Haemostasis, 2013)
Atherothrombosis is the major determinant of acute ischaemic cardiovascular events, such as myocardial infarction and stroke. Inflammatory processes have been linked to all phases of atherogenesis In particular, the identification of autoimmunity mediators in the complex microenvironment of chronic inflammation has become the focus of attention in both early and advanced atherogenic processes. Autoantibodies against self-molecules or new epitopes generated by oxidative processes infiltrate atherosclerotic plaques and were shown to modulate the activity of immune cells by binding various types of receptors. However, despite mounting evidence for a pathophysiological role of autoantibodies in atherothrombosis, the clinical relevance for circulating autoantibodies in cardiovascular outcomes is still debated. This review aims at illustrating the mechanisms by which different types of autoantibodies might either promote or repress atherothrombosis and to discuss the clinical studies assessing the role of auto-antibodies as prognostic biomarkers of plaque vulnerability.
Keywords: Atherosclerosis; auto-antibodies; inflammation; acute myocardial infarction; stroke